Analisis Manajemen Risiko IT Pada Sistem Informasi Akademik Menggunakan ISO 31000 - Fahlepi, Ridho; Fronita, Mona; Saputra, Eki; Hamzah, Muhammad Luthfi; Marsal, Arif; Daulay, Suandi (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The development of information technology is unavoidable. All aspects of human life require information technology. The use of information technology makes work easier to carry out. However, information technology also poses risks that can threaten the activities of an agency. The Pekanbaru College of Technology (STT) has implemented an Academic Information System (SIAKAD) to improve academic administration services, such as managing KRS, KHS, value input, schedules, and payments. Through interviews, it was identified possible risks that could disrupt business processes in the agency. The purpose of this study was to obtain an RPN (Risk Priority Number) value to provide recommendations for risk treatment in the Academic Information System (SIAKAD). The method used is ISO 31000 to measure the level of risk. The research stages include risk identification, risk analysis, calculation of RPN values, risk evaluation, and risk treatment. This research produces a level of risk from the highest to the lowest that can be used as a reference in the evaluation, treatment, and recommendations to overcome these risks.